1993
DOI: 10.1007/bf00297209
|View full text |Cite
|
Sign up to set email alerts
|

X-ray diffraction study on mammalian visceral smooth muscles in resting and activated states

Abstract: Structural changes of guinea pig taenia coli and rat anococcygeus muscle during contraction were studied by X-ray diffraction. The diffraction pattern of the taenia coli showed the 14.4-nm myosin reflection, the 5.9-nm actin layer-line and a diffuse equatorial peak at 1/11.4 nm-1. On application of carbachol, the muscle contracted and the intensity of the 14.4-nm reflection showed a concentration-dependent decrease: the maximum decrease was 24% at 2 x 10(-5) M. Such an intensity decrease was not observed in K-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
32
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 33 publications
2
32
0
Order By: Relevance
“…Quantitative electron microscopy revealed changes in the myosin filament content in some smooth muscles during contractile activation (17,23,71) and in adaptation to different cell lengths (24,35). These findings were corroborated by studies using birefringence (18,57) and X-ray diffraction (70). Note that in some smooth muscles, no evidence for myosin evanescence was found (17,27,71).…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…Quantitative electron microscopy revealed changes in the myosin filament content in some smooth muscles during contractile activation (17,23,71) and in adaptation to different cell lengths (24,35). These findings were corroborated by studies using birefringence (18,57) and X-ray diffraction (70). Note that in some smooth muscles, no evidence for myosin evanescence was found (17,27,71).…”
mentioning
confidence: 73%
“…With improved preparative techniques, later studies (4,15,16,59) were able to show that there was a significant number of thick filaments in the relaxed smooth muscle. The notion that thick filaments form and dissolve during the contraction-relaxation cycle was therefore abandoned and lay dormant for more than a decade until a series of studies published in the late 1980s and 1990s showed that at least in some smooth muscle, thick filament number increased as a result of contractile activation (17,18,70,71). The physiological significance of this finding was recognized in our proposals regarding possible mechanisms governing mechanical plasticity in smooth muscle (14,53).…”
Section: Early Observations Of Myosin Filament Evanescencementioning
confidence: 99%
“…Lability of myosin thick filaments has been demonstrated in some intact smooth muscle preparations (2,3,14,15), including that of airway smooth muscle (5). The labile nature can be seen in the variation of the thick filament density in cross sections of cells fixed under different experimental conditions (2,5,15).…”
Section: Discussionmentioning
confidence: 99%
“…The results suggest that in airway smooth muscle, filamentous myosins exist in equilibrium with monomeric myosins; muscle activation favors filament formation, and the resting calcium level is crucial for preservation of the filaments in the relaxed state. electron microscopy; muscle contraction; ethylene glycolbis(␤-aminoethyl ether)-N,N,NЈ,NЈ-tetraacetic acid; muscle plasticity IT HAS BEEN SUGGESTED that myosin thick filaments in relaxed smooth muscle are partially dissolved and reaggregate upon activation (2,3,14,15). Functional studies of airway smooth muscle have shown that thick filament lengthening could account for the increase in isometric force and the decrease in shortening velocity during the sustained phase of contraction (9).…”
mentioning
confidence: 99%
See 1 more Smart Citation